Peripheral odontogenic myxoma presenting as a gingival mass – a unique presentation with calcification. (20th May 2014) - Jose, M.; Basheer, S.; Balan, A.; Shameena, P.M.
Abstract: Myxomas of the jaws are considered to arise from odontogenic ectomesenchyme. They bear a close resemblance to the mesenchymal portion of a developing tooth. Peripheral odontogenic myxomas are very rare and less aggressive compared with the central odontogenic myxomas. No case of peripheral odontogenic myxoma with calcification has been reported to date. The purpose of this article is to document a case of peripheral odontogenic myxoma with calcification, located on the posterior maxillary gingiva.